Peter and the sword of mercy / 4. - Barry, Dave (Peter and the Starcatchers, 2009)
James, one of Peter Pan's original Lost Boys, asks George Darling and his wife Molly to help him find a secret cache of startstuff, which is hidden in a vault that can only be opened with a secret key kept with the crown jewels, but when Molly disappears, it is up to her daughter Wendy and Peter to rescue Molly, protect the treasure, and defeat Captain Hook.